Screening for subclinical atherosclerosis by noninvasive methods in asymptomatic patients with risk factors - Castellon X (Dove Medical Press, 2013)
Xavier Castellon, Vera BogdanovaDepartment of Cardiology, Private Hospital Athis Mons, Paris, FranceAbstract: Atherosclerosis is a leading cause of cardiovascular death due to the increasing prevalence of the disease and the impact of risk factors such as diabetes, obesity or smoking. Sudden cardiac death is the primary consequence of coronary artery disease in 50% of men and 64% of women. Currently the only available strategy to reduce mortality in the at-risk population is primary prevention; the target population must receive screening for atherosclerosis. The value of screening for subclinical atherosclerosis is still relevant, it has become standard clinical practice with the emergence of new noninvasive techniques (radio frequency [RF] measurement of intima-media thickness [RFQIMT] and arterial stiffness [RFQAS], and flow-mediated vasodilatation [FMV]), which have been used by our team since 2007 and are based on detection marker integrators which reflect the deleterious effect of risk factors on arterial remodeling before the onset of clinical events. These techniques allow the study of values according to age and diagnosis of the pathological value, the thickness of the intima media (RFQIMT), the speed of the pulse wave (RFQAS), and the degree of endothelial dysfunction (FMV). This screening is justified in asymptomatic patients with cardiovascular risk factors (hypertension, diabetes, obesity, dyslipidemia, and tobacco smoking). Studies conducted by RF coupled with two-dimensional echo since 2007 have led to a more detailed analysis of the state of the arterial wall. The various examinations allow an assessment of the degree of subclinical atherosclerosis and its impact on arterial remodeling and endothelial function. The use of noninvasive imaging in screening and early detection of subclinical atherosclerosis is reliable and reproducible and allows us to assess the susceptibility of our patients with risk factors and ensures better monitoring of atherosclerosis, thus reducing the occurrence of cardiovascular events in the long term.Keywords: radio frequency, RF QIMT, RF QAS, FMV, arterial age, velocimetry, MRI